Sub specialization and centralization of pediatric neuro-oncology services: a strategy to improve outcomes in low-resource settings - Baker, Abigail; Bhat K., Vasudeva; Moreira, Daniel C.; Qaddoumi, Ibrahim (Frontiers in Oncology, 2025)
BackgroundSubspecialization and centralization increase the quality of care in many medical subspecialties. It is expected to be standard of care in high-income countries. However, studies addressing the effect of subspecialization and centralization on the quality of pediatric neuro-oncology care in low-resource settings are lacking.MethodsWe determined the impact of subspecialization and centralization of pediatric neuro-oncology services on quality of care, survival outcomes, and quality of life by searching the Medline/PubMed literature database to identify relevant articles. We conducted this search using multiple English terms and keywords.ResultsPediatric brain tumors are rare, and the care of pediatric neuro-oncology patients is complex and requires a multidisciplinary team. Established pediatric neuro-oncology programs greatly increase patient survival, outcomes, quality of care, and hospital volume. Barriers to centralization may include the distance to travel and the financial burden of that travel, which could lead to underserved populations.ConclusionsSubspecialization and centralization of pediatric neuro-oncology services improves quality of care and patient outcome. More prospective research in this area is needed to determine the true impact of subspecialization and centralization in pediatric neuro-oncology in low-resource settings.